Kepatuhan menelan obat, merokok dan resiko kegagalan konversi (BTA positif) pada pasien tuberculosis - Mariawati Mariawati; Khoidar Amirus; Marliyana Marliyana (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
Active smokers, treatment compliance and sputum smear conversion failed among patients treated for active tuberculosisBackground: One of the infectious diseases that often affects people is pulmonary tuberculosis (pulmonary TB). World data, there are 10.4 million recent cases of tuberculosis or 142 cases / 100,000 populations, with 480,000 cases of failed conversions. Indonesia is a country with the second largest number of recent cases in the world after India. With the success of treatment in Indonesia, it is low at 85%. Data from Lampang Province, the number of new patients with pulmonary tuberculosis is reaching 110 per 100,000 populations. Data in Central Lampung Regency found 954 cases out of 20,184 people suspected (4.73%). Data in Poncowati Public Health Center in Central Lampung in 2018, conversion failure rates were quite high at 16 people out of 42 people with pulmonary TB (38.1% ), and the success of the treatment is also still low, at 76.2% (target> 90%).Purpose: Knowing relation factors active smoker, treatment compliance with failed sputum smear conversion among patients treated for active tuberculosis.Method: A quantitative study with the design by observational analytic. The samples in this study were 42 pulmonary TB patients. Data analysis in this study used the chi-square test.Results: Most respondents smoke <10 cigarettes per day (not at risk), 22 (52.4%). Most respondents obey the ingestion of drugs, which are 28 (66.7%). There was a correlation between active smoking (p-value = 0.002 and OR = 11.762) and medication adherence (p-value = 0.002 and OR = 9,167) with conversion failure in pulmonary tuberculosis patients.Conclusion: There were active smokers, treatment compliance, and sputum smear conversion failed among patients treated for active tuberculosis. It needs to further improve Directly Observed Therapy (DOT) support and the role of health workers in improving patient treatment compliance and motivation in quitting smoking.Keywords : Active smoking; Medication adherence; Conversion failure; Active tuberculosisPendahuluan: Salah satu penyakit menular yang sering diderita masyarakat adalah Tuberculosis paru (TB paru). Data dunia, terdapat 10,4 juta kasus baru tuberkulosis atau 142 kasus/100.000 populasi, dengan 480.000 kasus gagal konversi. Indonesia merupakan negara dengan jumlah kasus baru terbanyak kedua di dunia setelah India. Dengan angka keberhasilan pengobatan di Indonesia rendah, yaitu 85%. Data Provinsi Lampung, jumlah pasien baru tuberculosis paru yaitu mencapai 110 per 100.000 penduduk. Data di Kabupaten Lampung Tengah ditemukan sebanyak 954 kasus dari 20.184 orang suspek (4,73%).Data di Puskesmas Poncowati Lampung Tengah pada tahun 2018, angka kegagalan konversi cukup tinggi yaitu sebanyak 16 orang dari 42 orang penderita TB paru (38,1%), dan keberhasilan pengobatan juga masih rendah, yaitu 76,2% (target >90%). Tujuan: Diketahui hubungan para perokok aktif, kepatuhan menelan obat dan kegagalan konversi (BTA positif) pada pasien tuberculosis.Metode: Jenis penelitian kuantitatif, rancangan penelitian dengan analitik observasional. Sampel sejumlah 42 pasien TB paru. Analisis data pada penelitian ini menggunakan uji chi-square.Hasil: Sebagian besar responden merokok <10 batang perhari (tidak berisiko) yaitu sebanyak 22 orang (52,4%).Sebagian besar responden patuh dalam menelan obat, yaitu sebanyak 28 orang (66,7%). Terdapat hubungan antara merokok aktif (p-value = 0,002 dan OR= 11,762) dan kepatuhan menelan obat (p-value = 0,002 dan OR= 9,167) dengan kegagalan konversi pada pasien tuberculosis.Simpulan: Terdapat hubungan para perokok aktif, kepatuhan menelan obat dan kegagalan konversi (BTA positif) pada pasien tuberculosis. Perlu lebih ditingkatkannya dukungan PMO serta peran petugas kesehatan dalam meningkatkan kepatuhan berobat pasien dan motivasi dalam menghentikan kebiasaan merokok.